Gene networks from genome wide association studies for pigs reproductive traits - Verardo, Lucas Lima (2015)
Reproductive traits in pigs, such as number of stillborn (SB), total number born (TNB) and number of teats (NT), are widely included in breeding programs due their importance to the industry. As opposite to most association studies that consider continuous phenotypes under Gaussian assumptions, these traits are characterized as discrete variable, which could potentially follow other distributions, such as the Poisson. In addition, even though many genome wide association studies (GWAS) have been performed, only a few studies have explored biological meanings of genes identified. The present study provided a rich information resource about genes identified using genome wide association approaches for reproductive traits. The distribution analyses in genomic models, highlighted the importance in consider counting models for SB. Moreover, different sets of relevant SNPs and QTL blocks across and within the studies were identified leading to the possibility of different set of genes playing biological roles related to a single complex trait. Thereby, we highlighted the genomic diversity across population/environments to be observed in breeding programs in such a way that population/environments specific reference populations might be considered in genomic analyses. Based on these results, we demonstrated the importance of post-GWAS analyses increasing the biological understanding of relevant genes for complex traits.